2018
DOI: 10.1021/acsenergylett.8b01448
|View full text |Cite
|
Sign up to set email alerts
|

Exceeding 14% Efficiency for Solution-Processed Tandem Organic Solar Cells Combining Fullerene- and Nonfullerene-Based Subcells with Complementary Absorption

Abstract: For a highly efficient tandem organic solar cell, it is important for the subcells to minimize the absorption overlap and generate high and balanced currents. Considering the strong absorption and high external quantum efficiency at the short wavelength, developing a highly efficient blend system with a wide-bandgap (WBG) polymer as the donor and a fullerene derivative as the acceptor in the front cell would be an effective strategy. However, it is a challenge to obtain a high short-current density (J sc ) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…An exceptional PCE over 14.9% with strong EQE covering 400–1000 nm was achieved for optimized tandem OSC . By replacing front sub‐cell with PBD1:PC 71 BM, Wong and co‐workers reported tandem OSC with PCE of 14.2% with a high FF of 0.72 . Another outstanding PCE of 14.64% was recently achieved using a narrow bandgap FREA T2 with an unsymmetrical π‐bridge in rear sub‐cell in a tandem configuration …”
Section: Other Aspects Of Frea Oscsmentioning
confidence: 99%
“…An exceptional PCE over 14.9% with strong EQE covering 400–1000 nm was achieved for optimized tandem OSC . By replacing front sub‐cell with PBD1:PC 71 BM, Wong and co‐workers reported tandem OSC with PCE of 14.2% with a high FF of 0.72 . Another outstanding PCE of 14.64% was recently achieved using a narrow bandgap FREA T2 with an unsymmetrical π‐bridge in rear sub‐cell in a tandem configuration …”
Section: Other Aspects Of Frea Oscsmentioning
confidence: 99%
“…(PM6), [98,100] [101] [80] [102] and so on, and the thieno[3,4-b]thiophene (TT)-based low-bandgap polymers, such as poly [4,8- [86] poly [4,8- [98,102,103] poly [4,8- (PBDTTT-C-T), [60,104,105] poly[4,8-bis(5-(2-ethylhexyl) thiophen-2-yl)benzo[1,2-b:4,5-b 0 ]dithiophene-co-thieno[3,4-b] thiophene-2-carboxylate] (PBDTTT-E-T), [80,95] and so on. Using the BDD-based wide bandgap polymers in the bottom cell and TTbased polymers in the top cell as well as pairing with desirable fullerenes and NFAs have been demonstrated to be a successful choice to construct high-performance tandem OSCs.…”
Section: Polymer Donorsmentioning
confidence: 99%
“…[33] To circumvent that, the pH neutral PEDOT:PSS analogues of m-PEDOT:PSS and highly conductive poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PH100) with high viscosity were used. [21,33,[38][39][40]58,70,[75][76][77]85,97,99,102,122,[127][128][129]132,138,144,164,208] Zhou and coworkers found that PEDOT:PSS with surfactant deposited on top of nonfullerene-based tandem OSCs might lead to chemical reaction between PEDOT:PSS and the NFA (IT-4F), which would be detrimental to the device performance. [100] To avoid the direct deposition of PEDOT:PSS on top of the active layer, they introduced a hydrogen molybdenum bronze (H x MoO 3 ) layer between the bottom active layer and PEDOT: PSS.…”
Section: The Icls For Tandem Oscsmentioning
confidence: 99%
“…Polymeric solar cells (PSCs) have received wide attention due to their low cost, light weight, and solution fabrication for large‐area devices . With the development of novel active layer materials, the short‐circuit current ( J SC ) and fill factors ( FFs ) have been achieved beyond 20 mA cm −2 and 80%, respectively.…”
Section: Molecular Weights and Optical And Electrochemical Propertiesmentioning
confidence: 99%